Gerontological Counseling Trends in Adultspan Journal: 1999–2019. Issue 1 (3rd April 2021) - Fullen, Matthew C.; Chan, Christian D.; Jordan, Justin; Dobmeier, Robert A.; Gorby, Sean
Abstract : Using quantitative content analysis, we categorized 76 out of 154 articles (49.35%) published in Adultspan Journal from 1999 to 2019 as focused on gerontological counseling. This study explored publication trends for these articles and compared results with a larger study (Fullen et al., 2019) on publication trends for gerontological counseling across all counseling‐related journals.